2002
DOI: 10.1093/jxb/erf021
|View full text |Cite
|
Sign up to set email alerts
|

Effects of water deficit and its interaction with CO2 supply on the biochemistry and physiology of photosynthesis in sunflower

Abstract: Photosynthetic responses of sunflower plants grown for 52 d in ambient and elevated CO(2) (A=350 or E=700 micromol mol(-1), respectively) and subjected to no (control), mild or severe water deficits after 45 d were analysed to determine if E modifies responses to water deficiency. Relative water content, leaf water potential (Psi(w)) and osmotic potential decreased with water deficiency, but there were no effects of E. Growth in E decreased stomatal conductance (g(s)) and thereby transpiration, but increased n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
127
1
17

Year Published

2008
2008
2021
2021

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 210 publications
(156 citation statements)
references
References 53 publications
11
127
1
17
Order By: Relevance
“…O aumento, quando associado a baixos potenciais hídricos, causa uma progressiva redução na taxa fotossintética, até que esta se torne nula (LAWLOR, 2002). Dentre as causas para este efeito, são citados o decréscimo na eficiência da carboxilação, causado por uma inibição direta da maquinaria fotossintética devido ao dessecamento (KAISER, 1987), além de um déficit na taxa de regeneração da Rubisco (TEZARA et al, 2002). Após suspensão do estresse, para ambas as cultivares, aliada à abertura dos estômatos, houve uma retomada das trocas gasosas e queda acentuada na CiCO2.…”
Section: Resultsunclassified
See 2 more Smart Citations
“…O aumento, quando associado a baixos potenciais hídricos, causa uma progressiva redução na taxa fotossintética, até que esta se torne nula (LAWLOR, 2002). Dentre as causas para este efeito, são citados o decréscimo na eficiência da carboxilação, causado por uma inibição direta da maquinaria fotossintética devido ao dessecamento (KAISER, 1987), além de um déficit na taxa de regeneração da Rubisco (TEZARA et al, 2002). Após suspensão do estresse, para ambas as cultivares, aliada à abertura dos estômatos, houve uma retomada das trocas gasosas e queda acentuada na CiCO2.…”
Section: Resultsunclassified
“…Para a cultivar "RRIM 600", os percentuais foram, respectivamente, de 87,5%, 62,2% e 33,3%. O crescimento depende da divisão celular, do alongamento e da diferenciação, e todos estes processos são afetados pelo déficit hídrico, devido à perda da turgescência (TEZARA et al, 2002). Como o alongamento celular cessa antes da interrupção da fotossíntese, alguns autores sugerem que metabólitos osmoprotetores que possam ter sido acumulados durante o período em que o alongamento foi inibido pela falta de turgescência sejam depois utilizados para a síntese da parede celular e para outros processos associados com o crescimento, após a turgescência ter sido restabelecida (CHAVES et al, 2002).…”
Section: Resultsunclassified
See 1 more Smart Citation
“…Therefore a beneficial effect of elevated [CO 2 ] by ameliorating the adverse effects of drought stress was confirmed in sunflower. Tezara et al (2002) concluded that elevated [CO 2 ] only marginally increased net photosynthesis with limited effects on metabolism of plants growing under water deficit; however, by slowing plant transpiration, CO 2 fertilization decreased the rate and severity of water deficit.…”
Section: Interactions Between Temperature Water and Comentioning
confidence: 99%
“…The reduction in soil moisture may have led to lower water content in the leaves causing guard cells to lose turgor pressure and hence the size of stomatal pores are reduced (Tezara et al, 2002), causing stomatal closure (Singh et al, 2012). Avoidance allows plants to limit the effects of stress through adaptations such as wilting or leaf rolling.…”
Section: Avoidancementioning
confidence: 99%